Widespread positive selection on cetacean TLR extracellular domain. (February 2019) - Xu, Shixia; Tian, Ran; Lin, Yurui; Yu, Zhenpeng; Zhang, Zepeng; Niu, Xu; Wang, Xiaohong; Yang, Guang
Highlights: A total of 148 robust candidates of positive selection sites identified in the ECD of 10 TLRs. Positively selected sites enriched in cetacean habitat transitions from land to semi-aquatic and full-aquatic habitat. Comparable level of positive selection identified in viral TLRs and non-viral TLR during cetacean evolution. Cetacean TLR family members clustered into 10 major clusters according to each member in the phylogenetic tree. Abstract: Toll like receptors (TLRs), key members of innate immune system, can recognize a wide diversity of pathogens and initiate both innate and adaptive immune responses in vertebrate. Cetaceans must have faced new challenges of pathogens when their terrestrial relatives transitioned from the terrestrial to aquatic environment. Here, we sequenced the extracellular domain (ECD) of 10 TLRs in cetacean lineages because this region involved in the recognition of pathogens. A total of 148 sites ranging between 5–26 codons (0.01%–4.83%) were identified to be robust candidates of positive selection at the ECD of 10 TLRs. In addition, the majority (90.54%) of these positively selected codons were found to have radical amino acid changes, which strengthen the evidence of positive selection. Importantly, more radical amino acid changes in selected sites were enriched in the period of early evolutionary transition from land to semi-aquatic and from semi-aquatic to full-aquatic habitat, which might endow cetaceans with a faster adaptation to new pathogens as they transitioned into novel habitat. Interestingly, similar selective intensity was detected in both viral and non-viral TLRs in cetaceans, which was not in line with previous studies on primates and birds that reported stronger positive selection in non-viral TLRs than in viral TLRs. This result may be explained by the fact that cetaceans might have faced diversity of bacteria and viruses during its transitions from terrestrial to aquatic environment whereas both primates and birds probably being affected by only a restricted number of related viruses due to their homogeneous habitat.